Cell–cell interactions between monocytes/macrophages and synoviocyte-like cells promote inflammatory cell infiltration mediated by augmentation of MCP-1 production in temporomandibular joint - Ibi, Miho (Biosci Rep, 2018)
Many inflammatory cells are known to be home to inflamed temporomandibular joint (TMJ) tissues by stimulation with cytokines and chemokines produced by inflammatory lesions in the TMJ. However, how the inflammatory cells affect the progression of inflammation in TMJ synovial tissues after their homing to inflamed TMJ site is still uncertain. Here, we isolated and cultured TMJ synoviocyte-like cells (TMJSCs) from murine TMJ tissues. We demonstrated that interleukin 1β (IL-1β) up-regulated expression of monocyte chemoattractant protein 1 (MCP-1) in TMJSCs. In addition, we found that IL-1β-treated TMJSCs strongly promoted migratory activity of mouse monocyte/macrophage RAW264.7 cells through secretion of MCP-1. On the other hand, IL-1β up-regulated expression levels of intracellular adhesion molecule 1 (ICAM-1), a leukocyte adhesion ligand in TMJSCs. In addition, IL-1β promoted cell–cell adhesion between TMJSCs and RAW264.7 cells. Intriguingly, we also found that cell–cell interactions mediated through soluble factors other than IL-1β and cell–cell adhesion molecules between IL-1β-stimulated TMJSCs and RAW264.7 cells synergistically augmented secretion of MCP-1 from these cells. Therefore, these results suggested that the IL-1β-induced recruitment of monocyte/macrophage lineage cells to inflamed synovial membranes in TMJ was further augmented by the cell–cell interaction-induced secretion of MCP-1 from the inflammation site, possibly resulting in prolonged inflammatory responses in TMJ synovial tissue.